The use of emergent technologies to extract added value compounds from grape by-products - Coelho, M. (2020)
Background The current circular economy system-based sustainability and the social lifestyle trends, have led to a developed structure that is restorative or regenerative by purpose and innovation. It substitutes the end-of-life idea of a by-product adding value to it, shifts towards the usage of environmentally friendly solutions, eliminating the harmful chemicals, which impair reuse. Scope and approach Considering the wine production, which is one of the most critical agro-industrial sectors worldwide, generating large amounts of by-products with environmental impact, but also with high economic and nutritional potential. This review aims to evaluate the effects of alternative green technologies on the functionality and recovery of bioactive compounds (BCs) from wine by-products. Key findings and conclusions These agro-industrial by-products, e.g., skins and pulp remnants, are rich in BCs with health benefits such as supporting the immune system, anti-tumoral, and preventing cardiovascular diseases. Besides, the consumer has increased interest in diet and health, demanding suppliers to consider the reuse of agro-food by-products. Thus, the application of green recovery technologies eliminates the harmful effects comparing to conventional technologies, can be recycled into the food chain as functional additives for different products and applications, guaranteeing the sustainability and reducing the winemaking by-products.